2020
DOI: 10.1136/oemed-2020-106660
|View full text |Cite
|
Sign up to set email alerts
|

Employment and earnings trajectories before and after sickness absence due to major depressive disorder: a nationwide case–control study

Abstract: ObjectivesTo examine employment and earnings trajectories before and after the first sickness absence period due to major depressive disorder (MDD).MethodsAll individuals (n=158 813) in Finland who had a first sickness absence period (lasting longer than 9 days) due to MDD between 2005 and 2015 were matched with one randomly selected individual of the same age and gender with no history of MDD. Employment status and earnings were measured using register-based data annually from 2005 to 2015. Generalised estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…This association is known to be bidirectional, with low socioeconomic position (SEP) associated with future mental disorders,8–10 and mental disorders that have onset in childhood, adolescence or early adulthood followed by low SEP later in adulthood 11–15. Although most studies provide support for these associations, there is notable variability depending on the specific disorders examined; for example, whereas persons with substance misuse disorders or schizophrenia have a very low labour force participation rate,12 13 16–18 considerably higher rates have been reported among persons with mood or anxiety disorders 11 13 15 19 20…”
Section: Introductionmentioning
confidence: 99%
“…This association is known to be bidirectional, with low socioeconomic position (SEP) associated with future mental disorders,8–10 and mental disorders that have onset in childhood, adolescence or early adulthood followed by low SEP later in adulthood 11–15. Although most studies provide support for these associations, there is notable variability depending on the specific disorders examined; for example, whereas persons with substance misuse disorders or schizophrenia have a very low labour force participation rate,12 13 16–18 considerably higher rates have been reported among persons with mood or anxiety disorders 11 13 15 19 20…”
Section: Introductionmentioning
confidence: 99%
“…In line with our study, it has been previously suggested that marital status (or relationship status) is associated with the development and severity of MDD [ 51 ]. A link between MDD and unemployment was reported in an international study [ 52 ] and a Finland study [ 53 ]. It has also been shown that MDD and smoking are highly correlated [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 92%
“…This might partially explain our results, since psychiatric patients who were enrolled had been unemployed for a long time before this intervention took place, and presented with severe forms of psychiatric illness. A recent study (Hakulinen et al, 2021) of depressed patients found men experienced significantly higher rates of reduced employment and loss of earnings than women, even before the first period of illness, implying a deeper correlation between unemployment due to psychiatric issues and male gender. Moreover, the distribution of our sample may reflect the obstacles that still limit women’s access to the job market in Italy (50.1% employment rate for women vs. 68% employment rate for men – ISTAT, 2020).…”
Section: Discussionmentioning
confidence: 97%